2019
DOI: 10.31703/grr.2019(iv-iii).12
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Relational Coordination on Employee Creative Involvement: A Study of Public and Private Hospitals in Peshawar, Pakistan

Abstract: Relational coordination is an emerging HR-related concept based on the network of ties between task participants and is expected to produce favorable efficiency and quality outcome. The relational coordination-employee outcome is new research dimension in the relational coordination field. The objective of the study was to test if relational coordination leads to employee related outcomes. In terms of research methodology, we followed the positivism paradigm, used deductive approach, and quantitative method of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Previous studies have identified a substantial correlation between a person’s commitment to their profession and willingness to share their expertise ( Chen et al, 2020 ; Zada et al, 2021 ). Additionally, KS may be nurtured and developed if employees have developed favorable attitudes and gestures toward an organization, which requires a lot of internal desire ( Khan and Ali, 2019 ; Tahir et al, 2019 ). Ethical leaders play an important role in shaping and assisting the professional lives of their workers so that they can participate in KS behavior ( Kuenzi et al, 2019 ).…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…Previous studies have identified a substantial correlation between a person’s commitment to their profession and willingness to share their expertise ( Chen et al, 2020 ; Zada et al, 2021 ). Additionally, KS may be nurtured and developed if employees have developed favorable attitudes and gestures toward an organization, which requires a lot of internal desire ( Khan and Ali, 2019 ; Tahir et al, 2019 ). Ethical leaders play an important role in shaping and assisting the professional lives of their workers so that they can participate in KS behavior ( Kuenzi et al, 2019 ).…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…The Job Characteristics Model emphasizes that the perceived signi􀅫icance of one's work holds the potential for employees to 􀅫ind their jobs intrinsically motivating (Hackman & Oldham, 1976). This conclusion has been further substantiated by subsequent research (Tahir, Rahman & Saeed, 2019). Trott, (1996) expressed that the individuals who are available to important and deliberate connections, which are key parts of network, are bound to develop, learn, and accomplish at work and less inclined to encounter work burnout.…”
Section: Mediating Role Of Job Satisfactionmentioning
confidence: 94%
“…Innovation in the business sector has gained a top position in the firm stability, shortly innovation is an absolute demand without which the role of firms would remain unrated and it would not be able to gain place in any competitive confrontation. As product life cycles have shortened in this era, innovative capacity of firms has gained more importance than ever (Artz et al, 2010;Tahir, Rahman, & Saeed, 2019). For this reason, innovation has become a requisite objective for all firms (Lipit, 2006).…”
Section: Theoretical Frame Work and Hypotheses Developmentmentioning
confidence: 99%